2013
DOI: 10.1097/mcg.0b013e31827b9325
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Promoter Polymorphisms are Associated With Susceptibility to Gastric Cancer

Abstract: Our results suggest that polymorphisms in the OPN promoter are associated with the development of gastric cancer, and the combination of SNP -443 (T/C or C/C) and -616 (T/T or T/G) most significantly increases susceptibility to gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…OPN promoter polymorphisms are associated with susceptibility to gastric cancer. The combination of SNP −443 (T/C or C/C) and −616 (T/T or T/G) significantly increases susceptibility to gastric cancer (Lee et al, 2013). …”
Section: Opn In Clinical Evaluationsmentioning
confidence: 99%
“…OPN promoter polymorphisms are associated with susceptibility to gastric cancer. The combination of SNP −443 (T/C or C/C) and −616 (T/T or T/G) significantly increases susceptibility to gastric cancer (Lee et al, 2013). …”
Section: Opn In Clinical Evaluationsmentioning
confidence: 99%
“…An additional 4 articles, without control group data, were excluded. Thus, a total of 10 articles with 2,391 cases and 3,007 controls were included in the meta-analysis 20 21 22 23 24 25 26 27 28 29 . For the rs17524488 ( −156 GG/G ) polymorphism, 7 studies were available, including a total of 2,130 cases and 2,644 controls.…”
Section: Resultsmentioning
confidence: 99%
“…However, individual studies have yielded inconsistent or conflicting findings, possibly caused by limitations associated with an individual study. To shed light on these contradictory results and to more precisely evaluate the relationship among OPN gene polymorphisms and cancer risk, we performed a meta-analysis of 10 published studies 20 21 22 23 24 25 26 27 28 29 , the original regions of which were all from China, no other ethnicities or regions existed.…”
mentioning
confidence: 99%
“…In the pathological conditions of gastric cancer, overexpression of OPN has been repeatedly demonstrated to promote gastric cancer invasion and metastasis [33][34][35]. Moreover, genetic polymorphisms in the OPN promoter (-443C and -616T) were shown to increase gastric cancer susceptibility, suggesting a role for OPN in gastric cancer initiation [36]. We have previously shown that H. pylori can increase sOPN secretion from macrophages [12].…”
Section: Discussionmentioning
confidence: 97%